The stakes in ensuring the quality of the LMD education system in light of the concept of pedagogical support - ouchene, djamila (Journal of Social Sciences and Humanities, 2021)
The current study sought to review the reality and efforts of Algerian higher education institutions to achieve educational quality under the LMD formation system through the concept of pedagogical support, which comes within the framework of adaptating pedagogical and evaluation approaches, learning environments, creation of university structures for quality assurance, and the formulation of a national frame of reference for evaluation and the formation of human resources in order to respond To local development requirements.In the first place, the study attempted to shed light on the L M D formation system, its peculiarities, and the conditions for its local adoption, and then it sought to build a minimum level of theoretical consensus around a specific definition of educational quality, its standards and characteristics, in a way that the concept itself would be clear of all actors in the university sphere. The study also focused on Algeria's experience in the field of quality assurance and its endeavor to diversify and enhance the professionalization of training in the higher education sector and to develop its academic paths by introducing several mechanisms to ensure that outputs conform to the requirements of the labor market within a system that adopts the philosophy of pedagogical supportwhich guarantees accompanying the student throughout his training path beyond linking it to the economic and social environment.